Nutritional status, dietary intake and Soil-Transmitted Helminthiases among schoolchildren in selected rural villages in the Philippines - Wambangco-Tengco, Lorena S. (Philippine Journal of Nutrition, 2004)
This paper presents the anthropometric and iron status, dietary intake and prevalence of Soil-Transmitted Helminthiases (STH) among schoolchildren in selected villages in the provinces of Batangas ans Cebu in the Philippines. The data presented in this paper were collated from 3 studies of the Nutrition center of the Philippines. Data were available from 3,017 children for anthropometry, 2,928 for iron status, 1358 for dietary intake and 995 for prevalence of STH. This study aimed to determine the relationship of nutritional status with dietary intake and STH among schoolchildren. Weight was measured using a platform scale and height was determined using a microtoise or a wooden height board. Anthropometric status was determined by comparing the children's weight-for-age, height-for-age and weight-for-height z-scores with the National Center for Health Statistics standards. Iron status, using hemoglobin level as indicator, was determined through a HemoCue hemoglobinometer. Dietary intake was obatained through a 3-day 24-hour recall interview and intakes were compared against the gender-and age-specific Recommended Energy and Nutrient Intakes (RENI). Infection with STH was determined using the Kato-Katz technique. Thirty percent of the children were underweight, 37% were stunted and 3% were wasted. The prevalence of anemia was 37% (25% mild anemia, 12% moderate anemia and 0.07% severe anemia). The energy, protein, iron, vitamin A and vitamin C intakes were below the RENI per day. One out of 2 schoolchildren had STH, with 43% infected with Ascaris lumbricoides, 27% with Trichuris trichiura and 12% with hookworm. Significant associations were seen between nutritional status and dietary intake and STH. Schoolchildren in rural villages in the Philippines suffer from protein-energy malnutrition, anemia, inadequate food intake and STH. The energy, protein and iron intakes were associated with underweight and anemia. Energy and iron intakes were associated with stunting. Ascaris and hookworm infections were associated with stunting and Trichuris infection was associated with anemia. A comprehensive package of programs that includes micronutrient and food supplementation, deworming, sanitation and personal hygiene, and nutrition education should be considered for implementation in the rural elementary schools in the country.